Respiratory and heart rate patterns in infants destined to be victims of sudden infant death syndrome: average rates and their variability measured over 24 hours. Issue 6467 (16th February 1985) - Wilson, A J; Stevens, V; Franks, C I; Alexander, J; Southall, D P
Abstract : From a prospective study in which 24 hour recordings of the electrocardiogram and respiratory activity (abdominal wall movement) were made on a population of full term infants, 22 recordings were obtained from 16 infants who later were victims of the sudden infant death syndrome. The average heart rate, average heart rate variability, average breath to breath interval, and average breath to breath interval variability over the whole of each recording for the 22 recordings were compared with those from a control group of 324 infants selected at random from the rest of the population. No significance was found in the number of recordings from those infants who suffered the sudden infant death syndrome which lay outside the 5th-95th percentile range of the control group for the four variables studied. In a group comparison no difference was found between the sudden infant death syndrome group and the controls either in terms of the respiratory variables studied or in terms of the average heart rate variability. The results did, however, suggest that there may be a group difference in terms of the average instantaneous heart rate.